189 Virtual medication reviews in children and young people (CYP) with Attention Deficit Hyperactivity Disorder (ADHD) during the COVID-19 pandemic – A local service user experience survey. (17th August 2022) - Matthews, Yim-Yee; Wong, Max
Abstract : Aims: Traditional in-person ADHD medication review is part of the Neurodevelopmental Service led by a community paediatrician at a district general hospital in North Wales. Consequent to COVID-19 pandemic lockdown in March 2020, the service was delivered virtually to limit infection risk, via telephone and web-based video Attend Anywhere platform. Although aligned with the European ADHD Guidelines Group recommendations, there was no past report of user experience on such contingent service delivery. A survey was therefore designed to evaluate user satisfaction and preference on the new locally implemented virtual ADHD medication review clinics in CYP during the COVID-19 UK-wide lockdown. Methods: Families with ADHD CYP who had attended their first virtual ADHD medication consultation between 6 April to 12 May 2020 were surveyed via telephone in August 2021. Parent/carer and/or CYP with ADHD were requested for consent to provide independent satisfaction and preference ratings scores (5 very satisfied/strongly agreed, 4 satisfied/agreed, 3 neutral, 2 unsatisfied/disagreed and 1 very unsatisfied/strongly disagreed). Demography and clinical data were retrieved from respective clinic review letters. Microsoft Excel 2016 was used to analyse anonymised survey data. Results: Among nine clinics over the 6-week surveyed period, 47% (30/64) of the families of ADHD CYP of which 73% (22/30) male, were available and completed the survey. Responses were provided by all except one (29/30) mother and 37% (7/22 male and 4/8 female) of the surveyed ADHD cohort. The median (range) age in years for male was 13 (9 to 19) and female 14 (9 to 16). Their ADHD diagnosis ranged from 1 to 10 years with 63% identified with co-morbidities. Forty-percent experienced sleep issues with a-third benefiting for melatonin use. Among 93% of the cohort taking stimulants, 20% warrant medication only for schooling. Collective ratings were based on 10 telephone, 9 video and 11 both modes of virtual consultations. Greater satisfaction was reported from mothers than children on the quality of virtual consultations with highest ratings in screen (95% vs 86%) compared to access (70% vs 64%) and audio (79% vs 64%). Preferences on consultation modes for both mothers and children were similar with highest ratings for face-to-face (79% vs 82%), followed by video (61% vs 70%) and lowest via telephone (57% vs 55%) call. Conclusion: This parental and ADHD CYP survey results on the local virtually delivered ADHD medication reviews during the COVID-19 nationwide crisis, revealed despite high satisfaction on the quality of virtual consultations, greater for video screen than telephone audio only call, both users expressed greater preference for in-person consultations. Following COVID-19 de-escalation, while resuming the user preferred in-person ADHD medication review clinic service, video-link consultations with its past trial-established advantages and this survey of high user satisfaction in its quality, should be retained as an alternative clinic delivery mode.